In vivo anti-HIV activity of the heparin-activated serine protease inhibitor antithrombin III encapsulated in lymph-targeting immunoliposomes. - Mohammed Asmal; James B Whitney; Corinne Luedemann; Angela Carville; Robert Steen; Norman L Letvin; Ralf Geiben-Lynn (PLoS ONE)
Endogenous serine protease inhibitors (serpins) are anti-inflammatory mediators with multiple biologic functions. Several serpins have been reported to modulate HIV pathogenesis, or exhibit potent anti-HIV activity in vitro, but the efficacy of serpins as therapeutic agents for HIV in vivo has not yet been demonstrated. In the present study, we show that heparin-activated antithrombin III (hep-ATIII), a member of the serpin family, significantly inhibits lentiviral replication in a non-human primate model. We further demonstrate greater than one log(10) reduction in plasma viremia in the nonhuman primate system by loading of hep-ATIII into anti-HLA-DR immunoliposomes, which target tissue reservoirs of viral replication. We also demonstrate the utility of hep-ATIIII as a potential salvage agent for HIV strains resistant to standard anti-retroviral treatment. Finally, we applied gene-expression arrays to analyze hep-ATIII-induced host cell interactomes and found that downstream of hep-ATIII, two independent gene networks were modulated by host factors prostaglandin synthetase-2, ERK1/2 and NFκB. Ultimately, understanding how serpins, such as hep-ATIII, regulate host responses during HIV infection may reveal new avenues for therapeutic intervention.